2020
DOI: 10.17533/udea.acbi.v41n111a02
|View full text |Cite
|
Sign up to set email alerts
|

Metabolitos secundarios en Trichoderma spp. y sus aplicaciones biotecnológicas agrícolas

Abstract: Trichoderma es un hongo con múltiples aplicaciones biotecnológicas agrícolas. La más importante es la capacidad de inhibir el crecimiento, la esporulación y la germinación de esporas de hongos patógenos. Una gran variedad de investigaciones se centra en estudiar el potencial biológico y la formulación a base de especies de Trichoderma con actividad inhibitoria sobre microorganismos, lo que genera que estas prácticas sean más eficaces en un amplio rango de condiciones ambientales, de especies de plagas y de sis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 41 publications
2
5
0
Order By: Relevance
“…Consequently, its early detection in grains could avoid disease and loss of wheat crops. It is important to highlight that the environmental conditions for optimal F. sudanense growth obtained herein (high humidity and temperate temperatures) and in another study by the same authors 4 occur in the typical agro-ecological wheat region of Argentina until stem elongation, which is growth stage 30 according to Zadoks et al 39 As T. harzianum also grew under these same conditions, we suggest that both fungi can interact and, consequently, T. harzianum can dominate F. sudanense in field scenarios. These findings are of much importance today because biological control is an environmentally friendly and safer tool to be considered among current integrated disease management strategies applied to wheat crops.…”
Section: ■ Discussionsupporting
confidence: 58%
See 4 more Smart Citations
“…Consequently, its early detection in grains could avoid disease and loss of wheat crops. It is important to highlight that the environmental conditions for optimal F. sudanense growth obtained herein (high humidity and temperate temperatures) and in another study by the same authors 4 occur in the typical agro-ecological wheat region of Argentina until stem elongation, which is growth stage 30 according to Zadoks et al 39 As T. harzianum also grew under these same conditions, we suggest that both fungi can interact and, consequently, T. harzianum can dominate F. sudanense in field scenarios. These findings are of much importance today because biological control is an environmentally friendly and safer tool to be considered among current integrated disease management strategies applied to wheat crops.…”
Section: ■ Discussionsupporting
confidence: 58%
“…23 Previous ecophysiological studies in F. sudanense have demonstrated that fungus growth is affected by temperature and water availability in culture media. 4 However, the impact of such factors for F. sudanense in the presence of potential antagonists is currently unknown. Therefore, the impact of the main environmental requirements for fungal growth will provide a better understanding of its behavior in nature when it interacts with other fungi.…”
Section: ■ Introductionmentioning
confidence: 63%
See 3 more Smart Citations